2023
DOI: 10.3390/cancers15030954
|View full text |Cite
|
Sign up to set email alerts
|

ABL1/2 and DDR1 Drive MEKi Resistance in NRAS-Mutant Melanomas by Stabilizing RAF/MYC/ETS1 and Promoting RAF Homodimerization

Abstract: Melanomas harboring NRAS mutations are a particularly aggressive and deadly subtype. If patients cannot tolerate or the melanomas are insensitive to immune checkpoint blockade, there are no effective 2nd-line treatment options. Drugs targeting the RAF/MEK/ERK pathway, which are used for BRAF-mutant melanomas, do little to increase progression-free survival (PFS). Here, using both loss-of-function and gain-of-function approaches, we show that ABL1/2 and DDR1 are critical nodes during NRAS-mutant melanoma intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…A more recently identified negative regulators of oligodendrocyte differentiation is the MAPK/ERK pathway [ 27 , 45 , 46 , 47 ]. It was previously demonstrated that Ddr1 could modulate the activity of the AKT/ERK pathway and plays an important role in the migration and adhesion of cancer cells [ 30 , 48 , 49 ]. The Western blot analysis confirmed that inhibition of Ddr1 upregulates the ratio of p-ERK to total ERK without altering the AKT signaling pathway ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…A more recently identified negative regulators of oligodendrocyte differentiation is the MAPK/ERK pathway [ 27 , 45 , 46 , 47 ]. It was previously demonstrated that Ddr1 could modulate the activity of the AKT/ERK pathway and plays an important role in the migration and adhesion of cancer cells [ 30 , 48 , 49 ]. The Western blot analysis confirmed that inhibition of Ddr1 upregulates the ratio of p-ERK to total ERK without altering the AKT signaling pathway ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib also augmented vemurafenib anticancer activity against BRAF V600E melanoma xenografts by suppressing collagen remodeling [327]. It was also shown that the acquired resistance of NRAS mutant melanomas to trametinib was mediated by DDR1 activation [328]. DDR1 and DDR2 were overexpressed together with ephedrine receptors in double vemurafenib-and MEK inhibitor-cobimetinib-resistant BRAF V600E melanoma.…”
Section: Ddrmentioning
confidence: 98%